Rooting Response of Root Cuttings of some MPT Species under Low Cost Mist Conditions - Gera, Mohit; Gera, Neelu; Singh, V. K. (Indian Forester, 2000)
Rooting trial was carried out using root cuttings of seven multipurpose tree species in low cost mist chamber designed and developed in Tropical Forest Research Institute, Jabalpur. Maximum rooting (84.44%) was obtained in root cuttings of Dalbergia sissoo whereas Tectona grandis gave a very poor rooting response (10.00%). Albizia lebbek and Albizia procera, which are otherwise difficult to root species through branch cuttings, gave 56.67% and 66.67% rooting through root cuttings respectively. The findings of the present study highlight the importance of vegetative propagation through root cuttings and its substantial scope in tree improvement programmes. The technique enables successful vegetative propagation through root cuttings of multipurpose tree species including some of the difficult to root species without the assistance of growth hormones.